The Relationship Between Knowledge And Age Of Pregnant Women With High Risk Pregnancy In The Walengkabola Puskesmas Working Area - Wa Sarsini; Asruria Sani Fajriah (Journal of Health Science Community, 2026)
High risk pregnancy is a pregnancy that is likely to cause harm or complications to both the mother and the fetus bladder during pregnancy, childbirth or the puerperium when compared with normal pregnancy and childbirth (WHO 2021). To determine the relationship between knowledge and age of pregnant women with high-risk pregnancies in the working area of ​​​​the Walengkabola Health Center. The type of research used in this study is a descriptive analytic with a cross-sectional approach. The population used in this study are all pregnant women who visited the Walengkabolah Health Center in August 2022 to June 2023i.e. 118 people. Based on the results of the study, it can be concluded as follows: Most of the respondents had insufficient knowledge about high risk pregnancies, namely 30 people (55.5%) and pregnant women who had good knowledge, namely 24 people (44.4% ). Most of the high-risk pregnant women were aged ≤20 years and ≥35 years, namely 44 people (81.4%) and aged 20-35 years, a total of 10 people (18.5%) were pregnant women. Most of the respondents who had high risk pregnancies were as many as 36 people (66.6%) and 18 people (33.3%) who had low risk pregnancies. There is a relationship between knowledge of pregnant women and high risk pregnancies. There is a relationship between pregnant women and high-risk pregnancies.